The ID Dominance in Kathleen Glasgow’s Novel Girl in Pieces (2016) - Madiar, Melati Vaya Nugraha; Marlina, Leni (English Language and Literature, 2024)
Nowadays, it is important to provide a deeper understanding of the psychological dynamics underlying self-injurious behavior in the context of fictional narratives, so that it can provide new insights into our understanding of mental health problems and the prevention of such dangerous behavior. This study aims to examine how the id dominance of the character Charlie in Kathleen Glasgow's novel "Girl in Pieces" influences self-injury behavior. The research method used is qualitative. The theories used in this study are the Theory of Personality by Sigmund Freud (1923). The results show that Factors contributing to Charlie's id dominance include personality imbalance, lack of coping skills, and traumatic experiences.